2002
DOI: 10.1016/s0732-3123(02)00130-x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding metacognitive failure

Abstract: Running Head: Metacognitive failure 2 UNDERSTANDING METACOGNITIVE FAILUREThis paper reports on a study that investigated patterns of collaborative metacognitive activity in senior secondary school classrooms. Although peers working together on mathematical tasks may enjoy the metacognitive benefits of being able to monitor and regulate each other's thinking, collaboration does not guarantee that they will achieve a mathematically productive outcome. The notion of metacognitive "red flags", or warning signals t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 8 publications
(13 reference statements)
8
76
0
5
Order By: Relevance
“…4) is a potential cognitive barrier for students, a potential "blockage" or "red flag situation" (Goos 2002;Galbraith and Stillman 2006;Stillman 2011). "The weakest link in their modelling chain will set the limits on what they can do" (Treilibs et al 1980).…”
Section: Students' Modelling Activitiesmentioning
confidence: 99%
“…4) is a potential cognitive barrier for students, a potential "blockage" or "red flag situation" (Goos 2002;Galbraith and Stillman 2006;Stillman 2011). "The weakest link in their modelling chain will set the limits on what they can do" (Treilibs et al 1980).…”
Section: Students' Modelling Activitiesmentioning
confidence: 99%
“…Researchers have noted multiple problems when students were placed in situations with insufficient teacher guidance or when teachers did not capitalise on unexpected opportunities for learning (Rowland and Zazkis 2013;Stacey 1992). For example, Goos (2002) notes that although collaborative activity can help students to monitor and regulate each other's thinking, students can also unknowingly subvert such thinking if they have "passively accepted unhelpful suggestions, or ignored potentially useful strategies proposed by peers" (p. 300). The term inquiry is often used to describe a range of classroom environments from open-ended discovery learning to approaches that are highly structured and require little from students beyond following step-by-step instructions through an activity or pre-planned experiment.…”
Section: Challenges Of Inquiry-based Learningmentioning
confidence: 99%
“…Reflection forces designers to keep tabs on their process and products throughout the design process. Additionally, informed designers use metacognitive strategies to monitor their thinking and think about how their thinking has changed during the design process as a way to monitor their process (Crismond & Adams, 2012;Flavell, 1979;Goos, 2002;Perrenet, Bouhuijs, & Smits, 2000). Together, reflection and metacognition are essential skills students need, not only to monitor their design, but also to develop deeper levels of understanding about their skills and to understand their knowledge of problem solving and engineering design (Daly, Adams, & Bodner, 2012;Goos, 2002).…”
Section: Communicating Design Ideasmentioning
confidence: 99%
“…This could be a product of the format of the prompts and student habits of responding to teacher questions. However, it could also indicate that the prompts presented a metacognitive -red flag‖ (Goos, 2002) that prompted them to think metacognitively. For example, many students stated that they used to think one thing, but now thing something else or that they did not understand the problem at the beginning or identified that they know more now than they used to, especially in the Learned the depth of the problem and problem requirements and the Learned engineering design/problem solving themes.…”
Section: Reflection and Metacognitionmentioning
confidence: 99%